Diversity, metabolome profiling and bioactivities of benthic filamentous cyanobacteria isolated from coastal mangroves of Mayotte - Wang, Huibin; Halary, Sébastien; Duval, Charlotte; Bernard, Cécile; Troussellier, Marc; Beniddir, Mehdi A.; Brunel, Jean-Michel; Castaldi, Andrea; Caudal, Flore; Golléty, Claire; Martin, Coralie; Bourguet-Kondracki, Marie-Lise; et al. (Frontiers in Marine Science, 2023)
Cyanobacteria are important members of the dense biofilms that colonize available substrates in mangrove habitats worldwide. However, their taxonomic and chemical diversity as well biological activities have received little attention. Here, occurrence of cyanobacteria is evaluated in 27 biofilms collected from mangroves in Mayotte. Filamentous cyanobacterial strains are isolated and characterized using a 16S rRNA-based phylogenetic approach, advanced computational metabolomics tools, and antimicrobial, cytotoxic, anthelminthic and antibiofilm activities evaluation. Isolation procedures yielded 43 strains representing 22 species-level taxa, of which only three could be assigned to existing species. Some of these strains were among the most abundant cyanobacteria present in biofilms. PCR tests did not support the production of the main cyanotoxins. LC-MS/MS experiments were performed on the crude extracts of the 23 faster-growing strains, and construction of their molecular network showed a conspectus of their chemical diversity. Furthermore, by using both in silico tools ISDB-DNP (In silico Data Base–Dictionary of Natural Products) and MolDiscovery, godavarin K was annotated, a limonoid natural product previously isolated from the seeds of an Indian mangrove tree. This annotation was further confirmed by the marine database MarinLit, suggesting that cyanobacteria might be an alternative source of godavarin K and its four isomers. While no significant antimicrobial and cytotoxic activities were observed, some strains exhibited anthelminthic and antibiofilm activities that warrant further investigation, and may be relevant to biofilm ecology. Mangrove biofilms thus appear as untapped reservoirs of novel culturable cyanobacterial lineages, with bioactivities relevant to their biofilm lifestyle that could be of interest for bioinspiration.